God ebook A story of revelation. - Chopra, Deepak (2012)
Deepak Chopra, whose extraordinary Enlightenment series includes the phenomenal New York Times bestsellers Buddha and Jesus, delivers the most powerful installment yet: God. In this beautiful and thought-provoking teaching novel—a Story of Revelation—one of the Western World's acknowledged master teachers of Eastern philosophy and preeminent influencers in the realm of spirituality and religion reveals the evolving nature of God. Here is truth and enlightenment for the next generation of spiritual seekers; a book Deepak Chopra's millions of fans worldwide have been waiting for.